Cobalt nanoparticles on mesoporous MCM-41 and Al-MCM-41 by Supercritical CO2 Deposition - Aspromonte, Soledad Guadalupe (2012)
CoO and Co3O4 nanoparticles were uniformly dispersed inside mesoporous MCM-41 and Al-MCM-41 supports using supercritical CO2 reactive deposition. This method represents a one-pot reproducible procedure that allows the dissolution of the organocobalt precursor and supports impregnation in supercritical CO2 at 70 °C and 110 bar, followed by the precursor thermal decomposition into cobalt species at 200 °C and 160 bar. By the relative concentration of the cobalt precursor [cobalt (II) bis (η5-ciclopentadienil)], the load of cobalt nanoparticles was controlled and then determined by Inductively Coupled Plasma (ICP-OES). The synthesis of CoO and Co3O4 species inside the MCM-41 and Al-MCM-41 substrates was confirmed by X-ray Photoelectron (XPS) and Laser Raman Spectroscopies (LRS). By N2 adsorption and Small Angle X-ray Scattering (SAXS), it was determined that the hexagonal arrangement as well as the surface area and pore size of the substrates changed after the addition of cobalt. By means of X-ray mapping from SEM images, a homogeneous distribution of cobalt nanoparticles was observed inside the mesopores when the cobalt loading was 1 wt.%. In addition, spherical cobalt nanoparticles of average diameter close to 20 nm were detected on the outer surface of MCM-41 and Al-MCM-41 supports when the cobalt content was higher. On the other hand, by Transmission Electron Microscopy (TEM), it was possible to measure the interplanar distance of the crystalline plane of the outer nanoparticles, which was later compared with the theoretical distance values which allowed identifying the CoO and Co3O4 phases.